2020
DOI: 10.3390/chemosensors8030052
|View full text |Cite
|
Sign up to set email alerts
|

A Label-Free Fluorescent Sensor Based on the Formation of Poly(thymine)-Templated Copper Nanoparticles for the Sensitive and Selective Detection of MicroRNA from Cancer Cells

Abstract: In this work, a simple and label-free fluorescence “off” to “on” platform was designed for the sensitive and selective detection of microRNA (miRNA) in cancer cells. This method utilized a padlock DNA-based rolling circle amplification (P-RCA) to synthesize fluorescent poly(thymine) (PolyT) which acted as a template for the synthesis of copper nanoparticles (CuNPs) within 10 minutes under mild conditions. While the repeated PolyT sequence was used as the template for CuNP synthesis, other non-PolyT par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…let-7a was detected by an ssDNA padlock probe (Figure 11c). Once recognized, the resulting poly-T ssDNA was used as a template for the formation of fluorescent CuNPs, whose intense emission eliminated background signals showing a great degree of sensitivity (LOD of 70.6 fM) [89]. Magnetite (Fe 3 O 4 ) nanoparticles, associated with carbon (Fe 3 O 4 @C), were used as a quencher in a fluorescence-based detection of miR-20a.…”
Section: Other Metallic Nanoparticlesmentioning
confidence: 99%
“…let-7a was detected by an ssDNA padlock probe (Figure 11c). Once recognized, the resulting poly-T ssDNA was used as a template for the formation of fluorescent CuNPs, whose intense emission eliminated background signals showing a great degree of sensitivity (LOD of 70.6 fM) [89]. Magnetite (Fe 3 O 4 ) nanoparticles, associated with carbon (Fe 3 O 4 @C), were used as a quencher in a fluorescence-based detection of miR-20a.…”
Section: Other Metallic Nanoparticlesmentioning
confidence: 99%
“…Compared to SNV detection, the simultaneous specific detection of miRNA homologous sequences is more challenging. Recently, researchers have tried to develop new SNV detection methods for simultaneous specific detection of miRNA homologous sequences. , For example, Ma et al reported a method for the specific detection of let-7a through ligase mediated rolling circle amplification (RCA). Generally, the identification of similar sequences was achieved by designing similar probes in multiple parallel detection systems.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence methods have attracted widespread attention due to their advantages of a fast response, high sensitivity and simple equipment [8][9][10]. The fluorescence material plays an important role in the sensitivity, selectivity and sensing speed of a fluorescence method [11,12]. There are some reports on the determination of TC by sensors based on fluorescence materials, such as carbon dots [13], Eu 3+ -functionalized silicon nanoparticles [14] and SYBR Green I [15].…”
Section: Introductionmentioning
confidence: 99%